2020
DOI: 10.1038/s41467-020-17038-2
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater level observations in 250,000 coastal US wells reveal scope of potential seawater intrusion

Abstract: Seawater intrusion into coastal aquifers can increase groundwater salinity beyond potable levels, endangering access to freshwater for millions of people. Seawater intrusion is particularly likely where water tables lie below sea level, but can also arise from groundwater pumping in some coastal aquifers with water tables above sea level. Nevertheless, no nationwide, observation-based assessment of the scope of potential seawater intrusion exists. Here we compile and analyze~250,000 coastal groundwater-level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(35 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…However, with the increase in water demands, groundwater pollution caused by seawater intrusion [3][4][5][6][7], waste disposal of urban residents, and industrial and agricultural production [8][9][10] have caused severe threats to freshwater resource. Seawater intrusion is widely regarded as a common environmental problem affecting groundwater in coastal areas [11][12][13]. With 1% mixing of seawater would render the groundwater nonpotable and further induce soil salinization, ecological degradation, and decline in the quality of agricultural and industrial products [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, with the increase in water demands, groundwater pollution caused by seawater intrusion [3][4][5][6][7], waste disposal of urban residents, and industrial and agricultural production [8][9][10] have caused severe threats to freshwater resource. Seawater intrusion is widely regarded as a common environmental problem affecting groundwater in coastal areas [11][12][13]. With 1% mixing of seawater would render the groundwater nonpotable and further induce soil salinization, ecological degradation, and decline in the quality of agricultural and industrial products [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The differences between Figures 10A and 10B imply that the pumping activity has reversed the groundwater flow from a gulfward direction to a landward direction. As Jasechko et al (2020) has shown, the saltwater intrusion in Southwest Louisiana can be connected to groundwater level decline in inland areas. However, the origin of the salt water is not the Gulf of Mexico as they argued.…”
Section: Groundwater Level Analysismentioning
confidence: 99%
“…This change in gradient provides a gateway for saltwater to migrate inland and contaminate freshwater sources. Jasechko et al (2020) demonstrated that many of the aquifers along the Gulf Coast, including the Chicot aquifer in Louisiana, are susceptible to saltwater intrusion due to this landward HG. Borrok and Broussard (2016) highlight historical areas of saltwater encroachment within the Chicot aquifer.…”
Section: Study Sitementioning
confidence: 99%